(untitled) (Al-Farooq Journal of Sciences, 2026)
The purpose of this article is to examine the many syllabuses that are used to instruct both native and non-native English speakers. In order to describe each form of syllabus according to its emergence in the epistemology of syllabus design and pedagogical trends in teaching English worldwide, the researcher employed a chronological approach. The paper emphasized theories of language and learning, features of each syllabus, and advantages and disadvantages of the syllabi under discussion. Additionally, emphasis was placed on illuminating the connections between instructional methods and techniques and syllabus types. Examples of syllabi design was also discussed. The researcher made an effort to include writings from academics and authors who supported each course. This article’s material was presented using a list of key titles and explanations of the curriculum. For additional inspiration, primary and secondary sources were consulted.